Graphene-Assisted Sensor for Rapid Detection of Antibiotic Resistance in Escherichia coli - Li, Chunlei; Sun, Feng (Frontiers in Chemistry, 2021)
In recent years, antibiotic-resistant bacteria caused by antibiotic abuse in the medical industry have become a new environmental pollutant that endangers public health. Therefore, it is necessary to establish a detection method for evaluating drug-resistant bacteria. In this work, we used Escherichia coli as a target model and proposed a method to evaluate its drug resistance for three antibiotics. Graphene dispersion was used to co-mix with E. coli cells for the purpose of increasing the current signal. This electrochemical-based sensor allows the evaluation of the activity of E. coli on the electrode surface. When antibiotics were present, the electrocatalytic reduction signal was diminished because of the reduced activity of E. coli. Based on the difference in the electrochemical reduction signal, we can evaluate the antibiotic resistance of different E. coli strains.